State of the Union 1994 : the Clinton administration and the nation in profile - Caplan, Richard; Feffer, John, (ed) (Boulder : Westview Press, 1993)
Political Sc. and Public Admin
Bibliography : p.
1996-03-24
Keywords: Politics; Government; Foreign relations; United State of America